Republic of Kosovo : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This staff report on the Republic of Kosovo's 2013 Article IV Consultation focuses on economic and financial developments. Kosovo's economy is excessively dependent on inflows from the diaspora. It is found that while these inflows support incomes, they finance primarily consumption and investments in nontradables, such as real estate or services, and contribute little to the build-up of productive capacity. Goods exports are less than 10 percent of GDP and concentrated in sectors with a low-value added component, notably metals. A coherent strategy is needed to improve competitiveness, foster the development of a tradable sector, and lay the basis for self-sustained growth.